2016
DOI: 10.1038/jhg.2016.151
|View full text |Cite
|
Sign up to set email alerts
|

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails

Abstract: Background Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes which were initially considered incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…The most common findings were hypoplastic or absent nails. Short fingers and nails in an individual with intellectual disability should therefore increase the index of suspicion of IGDs in addition to Coffin‐Siris syndrome (MIM: PS135900), DOORS syndrome (MIM: 220500), Zimmermann‐Laband syndrome (MIM: PS135500), and Kaufman oculocerebrofacial syndrome (MIM: 244450) …”
Section: Resultsmentioning
confidence: 99%
“…The most common findings were hypoplastic or absent nails. Short fingers and nails in an individual with intellectual disability should therefore increase the index of suspicion of IGDs in addition to Coffin‐Siris syndrome (MIM: PS135900), DOORS syndrome (MIM: 220500), Zimmermann‐Laband syndrome (MIM: PS135500), and Kaufman oculocerebrofacial syndrome (MIM: 244450) …”
Section: Resultsmentioning
confidence: 99%
“…Single gene disorders were identified in 14 individuals from nine families. Autosomal recessive mutations were identified in NSUN2 , LIG4 , BRCA1, UBE3B, RNU4ATAC, and PCNT1 (Dieks, Baumer, Wilichowski, Rauch, & Sigler, ; Kariminejad et al, ; Krøigård et al, ; Martinez et al, ; Sawyer et al, ; Table ). Autosomal dominant de novo mutations were reported in ACTB and STAT3 (Beitzke et al, ; Johnston et al, ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…These included two sets of concordant monozygous twins (Möhrenschlager, Beham, Abeck, & Ring, ; Urquhart et al, ); one pair with a 19q13 microdeletion. There were three siblings with homozygous NSUN2 mutations (Martinez et al, ), two siblings with biallelic LIG4 mutations (Gruhn et al, ), a sibling pair with biallelic mutations in RNU4ATAC (Krøigård et al, ) and a sibling pair with UBE3B mutations (Kariminejad et al, ). There was also a set of brothers where DS was considered, but subsequently thought unlikely based on detailed clinical assessment (Lemire, Stoeber, Anselmo, & Lowry, ), and an Italian sibling pair was concordant for many features of DS, but was considered to have a blepharophimosis‐intellectual disability syndrome after an extensive work‐up (Dentici et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaufman oculocerebrofacial syndrome (KOS), a rare autosomal recessive type of the BMRS, was first described in 1971, but it was not until 2012 that its genetic cause was discovered via the identification of biallelic mutations in the ubiquitin ligase E3B encoding gene UBE3B (Basel‐Vanagaite et al, ; Flex et al, ; Kaufman et al, ) With only 15 published patients with biallelic UBE3B mutations reported so far, knowledge on the phenotypic and molecular characteristics of KOS is still expanding. (Basel‐Vanagaite et al, , ; Flex et al, ; Kariminejad et al, ; Pedurupillay et al, ) Apart from the original four patients of Kaufman, five patients with the clinical diagnosis of KOS have been reported between 1971 and 2013 (Briscioli, Manoukian, Selicorni, Livini, & Lalatta, ; Figuera, Garcia‐Cruz, Ramirez‐Duenas, Rivera‐Robles, & Cantu, ; Jurenka & Evans, ; Murano, ). The patient of Briscioli et al () had no blepharophimosis and was later subject of UBE3B sequencing by Flex et al () but no disease‐causing mutation was identified.…”
Section: Introductionmentioning
confidence: 99%